Lumbee Indians in the Jim Crow South : Race, Identity, and the Making of a Nation - Lowery, Malinda Maynor (Book collections on Project MUSE., 2010)
With more than 50,000 enrolled members, North Carolina's Lumbee Indians are the largest Native American tribe east of the Mississippi River. Malinda Maynor Lowery, a Lumbee herself, describes how, between Reconstruction and the 1950s, the Lumbee crafted and maintained a distinct identity in an era defined by racial segregation in the South and paternalistic policies for Indians throughout the nation. They did so against the backdrop of some of the central issues in American history, including race, class, politics, and citizenship. With more than 50,000 enrolled members, North Carolina's Lumbee.